Variation in single kernel hardness within the wheat spike - Miller, Christopher L. (Kansas State University, 2008)
Variation in wheat kernel hardness is influenced by several factors including genetic expression and environmental conditions. However, these factors explain only a portion of the observed variation. Thus, there are unknown contributors to this important physical property. The following experiments investigated growing locations between farms and within the spike as a source of variation. Four commercial varieties of Hard Red Winter (HRW) wheat were chosen for evaluation; Jagger, Jagalene, Overley, and 2137. In total, 374 wheat spikes were collected from three farms participating in the Kansas State University Research and Extension- 2007 Crop Performance Tests (KSCPT). For analyses, each kernel was removed and cataloged by spikelet and floret position. A total of 10,240 kernels were uniquely identified by variety, farm, plot, spike, spikelet and floret position. Using the single kernel characterization system (SKCS), kernels were crushed to determine the hardness, diameter, weight, and moisture content. The variability of each measured attribute was greatest between spikes of a given variety. Measured attributes exist in gradients along the spike, with the top and bottom portions being most variable. This research broadens our knowledge of wheat kernel variation, and results from this experiment may contribute to improved methods for single kernel analysis.
Keywords: Wheat; Hardness; Spikelet; Agriculture, Agronomy (0285); Agriculture, Food Science and Technology (0359)